Effect of Organic Sources of Nutrition in Performance of Tomato and Soil Properties Inside Plastic House - Shrestha, Shukra Raj; Bhandari, Kishor; Thakur, Manish Kumar; Yadav, Surendra Prasad; Yadav, Digambar; Dahal, Bikash; Sherpa, Damali (Agriculture Development Journal, 2025)
The experiments were conducted during September-March over two years, in 2022-23 and 2023 24 under plastic house at Directorate of Agricultural Research, Tarahara, Sunsari to evaluate the responses of organic sources of nutrition on growth, yield, yield attributes and fruit quality of tomato and to monitor changes in soil properties. Experiments were laid out in a Randomized Complete Block Design (RCBD) with eight treatments comprising organic manures and compost like farmyard manure, vermicompost, poultry manure, goat manure, mustard oil cake, self-prepared compost and Jeevamrut including the control plots without any fertilizers. Each treatment was replicated thrice. The doses of manures and compost were calculated to fulfill the nitrogen requirement recommended for Tomato cv. ‘Srijana’. The pooled analysis revealed that the plant height, days to first flower, number of fruits per cluster, number of fruits per plant and fruits yields showed significant variation among the treatments. The highest fruit yield (2.93 kg/plant i.e.74.92 t/ha) was obtained from plants treated with vermicompost followed by the plants receiving farmyard manure (2.88 kg/plant). Treatments did not show significant change in the Total soluble solids (TSS) and titratable acidity (TA) of tomato fruits. The soil samples of each experimental plot were analyzed for chemical and physical properties at the beginning and after the crop’s final harvest in both the years. The significant improvement in total nitrogen, available phosphorus, available potassium and soil organic matter was observed in fertilized plots over the control during trial period.